Cellulose Hydrolysis of Mask Waste Using Aspergillus niger and Eco-Friendly Microwave Pretreatment - Gilbran, Adam; Nafilah, Syahraini; Layalia, Afina Rista; Arsyad, Wifqul Muna; Darmawan, Andi; Setiawan, Risqi Prastianto; Irviandi, Risnu; Kusdiyantini, Endang; Nurauliyaa, Aida Habibah; Anda, Martin; Sasongko, Nugroho Adi; Wahyono, Yoyon (Universitas Diponegoro, 2025)
The management of used medical mask waste has become a significant issue due to the increased volume of waste during and after the pandemic. Medical mask waste contains cellulose compounds that can be converted into derivatives such as glucose, which are then processed into bioethanol as an alternative energy source. This study aims to hydrolyse medical mask waste using cellulase enzymes from Aspergillus Niger to produce glucose. The cellulase enzyme composition was varied (5 ml, 15 ml, and 25 ml) to determine the optimal hydrolysis conditions. The glucose produced was measured using DNS reagent assay with spectrophotometry at a wavelength of 540 nm. The highest amount of glucose was obtained under optimal conditions with 25 ml of cellulase enzyme after 48 hours of hydrolysis, amounting to 88.16 ppm. Subsequently, the glucose from hydrolysis was fermented using Saccharomyces cerevisiae, and the fermentation product was analysed for ethanol concentration using GC-FID. The products of fermentation ware 0.017% ethanol concentration from mask waste fermentation. Hydrolysis is an environmentally friendly alternative solution for handling mask waste.